The prevention of oral disease - Murray, John J.; Nunn, June H.; Steele, J. G. (James George) (Oxford University Press, 2003)
The new edition of Prevention of Oral Disease remains the only comprehensive textbook covering all aspects of dental prevention. Chapters covering conventional preventive issues such as diet and fluorides are complemented by innovative new or revised material in a wide range of areas, including mucosal disease, the pulp and endodontics and periodontal disease. Generic subjects such as the social dimension of oral health and health promotion underpin the clinically basedchapters. The book is relevant to anyone who has to provide or understand prevention, irrespective of their clinical disciplin.